Lipid metabolism in Decapods: DGAT activity, total lipid content, transcripts of relevant enzymes - Marie Koch; Jan Tebben; Reinhard Saborowski (PANGAEA, 2023)
The storage lipid metabolism of two caridean shrimp species (Crangon crangon and Pandalus montagui) was studied through a combination of enzyme assays, total lipid determination and transcriptome analyses. The initital sampling was carried out in June, July and August 2021 by the research vessel R/V Uthörn. Freshly caught shrimps from the North Sea were measured, weighted and dissected and brought back to the laboratory facilites of the Alfread-Wegener-Institute, Bremerhaven, Germany. Individual midgut glands were weighted to determine the wet mass and freeze-dried. Dry mass was termined and lipids were extracted after Hagen (2000, see in Postel et al. 2000). The total lipid content of individual midgut glands of Crangon crangon and Pandalus montagui was determined gravimetrically. The synthesis of the storage lipid triacylglycerol (TAG) was measured in pooled microsomal fraction of midgut gland tissue of both shrimp species through the activity of the enzyme diacylglycerol acyltransferase (DGAT) at 37 °C in a water bath (McFie & Stone 2011). Here a fluorescent activated fatty acid (NBD-palmitoyl-CoA, 810229 Avanti Polar Lipids) was used. Lipids in the reaction mix were extracted and lipid classes separated on a thin layer chromatography plate. DGAT activity was measured through arbitrary fluorescent units (AFU/min/mg protein) of the correscponding TAG product. Annotated transcriptomes of both species (C. crangon Bioproject: PRJNA479562, NCBI; P. montagui Bioproject PRJNA798226, NCBI) were screened for enzymes involved in the lipid metabolism. Transcripts identified as relevant enzymes using BLAST were translated into amino acid sequences.